Peranan Kepala Desa Terhadap Pembangunan Infrastruktur Jalan Pada Desa Pulau Sejuk Kecamatan Datuk Lima Puluh Kabupaten Batu Bara - Arifah Arifah; Budi Hartono; Marlina Deliana (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2023)
Infrastructure development is crucial in fostering economic growth. The development undertaken by the village government significantly influences the road infrastructure in Pulau Sejuk Village. With several damaged roads, the researcher was intrigued to explore the Role of the Village Head in Road Infrastructure Development in Pulau Sejuk Village and delineate the supporting and inhibiting factors of the Village Head's Role in Road Infrastructure Development. To address the research questions, the researcher employed Soekanto and Sulistyowati's (2017) theory, emphasizing planning, implementation, and monitoring. Data collection involved interviews, observations, documentation, and qualitative analysis following Sugiyono's (2010) methodology. The findings reveal that the village head's role in planning road infrastructure development has been well laid out, but its execution is pending. Direct or indirect supervision by the village head and village apparatus in road development has yet to materialize due to the absence of road repairs. The Village Head of Pulau Sejuk needs to pay closer attention to road development to ensure smooth infrastructure implementation.